Automated anti-Mullerian hormone measurement: data review to provide insights and interpretation. (3rd June 2021) - Homburg, R.; Rao, U.; Malamas, F.; Palouki, P.; Gudi, A.; Shah, A.; Brooks, S.; Drakeley, A.; Faye, S.
Abstract: Objective and Methods: All women seen at the Homerton Fertility Center, London (Site 1, n  = 1787) and Hewitt Fertility Center, Liverpool (Site 2, n  = 1258) in 15 months had serum AMH measured using the Access 2 fully automated benchtop immunoassay analyzer(Beckman Coulter Inc, ) and a subset ( n  = 2031) were followed up to determine eggs collected and clinical pregnancy rates (CPR). Results: AMH results were pooled and a table with 2.5 and 97.5 percentiles for each age group constructed. Based on Youden index, the optimal cut off for low responders (0–3 eggs), was 5.5 pmol/l (87% sensitivity, 55% specificity) and for high responders (>15 eggs) 15.6 pmol/l (78% sensitivity, 57% specificity). AMH correlated with number of eggs collected ( r  = 0.48) and clinical pregnancies ( r  = 0.14), ( p  < .0001). Conclusions: The table of AMH levels measured using the Access 2 fully automated immunoassay system according to age may be used as a reference and cutoff levels for high and poor responders are clearly defined to help tailor controlled ovarian stimulation, maximizing efficiency and ensuring patient safety. The use of a random access automated immunoassay system means that blood sampled on arrival can produce an AMH result in 40 mins by the time the subject enters the doctor's clinic together with other relevant endocrine markers.